Implementasi Kegiatan PEKAS (Pekan Kreasi Sabtu) Berbasis Kurikulum Merdeka untuk Pengembangan Minat dan Bakat Peserta Didik di SDN 76 Kota Bengkulu - Wedianti, Mamik; Purtuna Sakti, Melan; Sri Marisa, Rika; Putri, Yarsi (Yayasan Darussalam Bengkulu, 2025)
This study aims to examine the implementation of the PEKAS (Saturday Creativity Week) program based on the Independent Curriculum in developing students' interests and talents at SDN 76 Bengkulu City. The PEKAS program is an extracurricular activity held every month on Saturdays, with the aim of providing space for students to explore their potential and creativity outside of formal learning. This study uses a qualitative descriptive approach with data collection methods through interviews, observations, and documentation. The data obtained were analyzed to describe the impact of the PEKAS program on the development of students' interests and talents. The results of the study indicate that the PEKAS program has succeeded in increasing students' motivation and self-confidence in expressing their creativity. Positive feedback from teachers, parents, and students indicates that this activity provides significant benefits in supporting the development of interests and talents, in line with the principles of the Independent Curriculum which prioritizes learning based on individual needs and potential. Therefore, PEKAS can be an effective model in implementing the Independent Curriculum and developing student potential holistically. This study contributes to the understanding of the importance of extracurricular activities in supporting more inclusive and creative education.